The Effectiveness of Meloxicam Adjuvant Therapy against Negative Symptoms and Neutrophil Lymphocyte Ratio (NLR) in Schizophrenic Patients - Melati, Katarina Bernadet Dinda Sekar; Hardaetha, Adriesti; Kusuma, Wijaya (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2023)
Highlights:1. The NLR value can show the role of neuroinflammation in schizophrenic patients.2. Meloxicam as adjuvant therapy can improve negative symptoms and changes in the NLR in schizophrenic patients. AbstractIntroduction: Neutrophil-lymphocyte ratio is a simple and affordable marker of inflammation that has recently been widely used to assess systemic inflammation in psychiatric patients. This study aimed to determine and analyze the effectiveness of meloxicam as adjuvant therapy to improve negative symptoms and changes in the neutrophil-lymphocyte ratio (NLR) in schizophrenic patients. Methods: This was a quasi-experimental study using a single-blind, pretest–post-test design. Subjects were determined using a purposive sampling technique based on inclusion criteria. This study examined 34 samples and divided them into two groups. The treatment group consisted of 17 subjects who received adjuvant therapy with meloxicam 15 mg/day for 4 weeks and 17 subjects in the control group. Data collection was obtained from medical records, interviews, field notes, positive scale, negative scale, and general psychopathology scale (PANSS) assessment sheets, and blood NLR examinations. Data analysis used SPSS 25.0.Results: The negative subscale PANSS score in the treatment group decreased lower than in the control group, with p-value = 0.640. However, the decrease in NLR values was more significant in the treatment group than in the control group, with p-value = 0.094. There was a decrease in the negative subscale PANSS scores and clinical NLR scores, but it was not statistically significant.Conclusion: Adjuvant therapy with Meloxicam, given once a day for four weeks, had an effect on decreasing the negative subscale PANSS score and NLR scores for schizophrenic patients at Dr. Arif Zainudin Regional Mental Hospital (RSJD), Surakarta, clinically, but it was not statistically significant.